2018
DOI: 10.20396/san.v25i1.8651123
|View full text |Cite
|
Sign up to set email alerts
|

Ácidos Orgânicos e Compostos Clorados para Controle de Salmonella spp. em frangos

Abstract: O objetivo deste trabalho foi avaliar a atividade de ácidos orgânicos e compostos clorados comerciais para o controle de Salmonella spp. A concentração inibitória mínima (CIM) do dióxido de cloro, dicloro isocianurato de sódio e ácidos tricloro isocianúrico, lático e peracético foi determinada para cepas padrões de S. Enteretidis, S. Typhimurium e a S. Heidelberg e avaliada com 54 cepas isoladas de frigorífico. O produto com melhor desempenho foi avaliado em água de chiller artificialmente contaminada com Salm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Machado et al (2013), evaluated the treatment of pork shanks with immersion in acid solution (0.1% citric acid) for 5 s, concluded that the isolated action of this treatment alone was not satisfactory to control Salmonella Typhimurium, although the combined use of steam (15 s) followed by the use of acid solution was more effective. Zabot et al (2018), treated chicken thighs with 20 g/L (2.0%) lactic acid solution and observed the growth inhibition (100%) of Salmonella spp. in the samples.…”
Section: Resultsmentioning
confidence: 99%
“…Machado et al (2013), evaluated the treatment of pork shanks with immersion in acid solution (0.1% citric acid) for 5 s, concluded that the isolated action of this treatment alone was not satisfactory to control Salmonella Typhimurium, although the combined use of steam (15 s) followed by the use of acid solution was more effective. Zabot et al (2018), treated chicken thighs with 20 g/L (2.0%) lactic acid solution and observed the growth inhibition (100%) of Salmonella spp. in the samples.…”
Section: Resultsmentioning
confidence: 99%
“…The latter showed an effect applied to chiller water artificially contaminated with Salmonella spp.. Although not allowed by Brazilian law, the use of lactic acid in chicken slaughterhouses is already a practice adopted in the United States of America (ZABOT et al, 2018).…”
Section: Characterization and Properties Of Organic Acidsmentioning
confidence: 99%